Phase velocity measurements in bubbly liquids using a fiber optic laser interferometer - Cheyne, SA; Stebbings, CT; Roy, RA (Acoustical Society of America, 1995)
Acoustic phase velocity measurements of a bubbly liquid in a cylindrical tube have been made with a fiber optic laser interferometer (FOLI) and hydrophones. Past experimental configurations of sound propagation studies in tubes filled with air–water mixtures consisted of hydrophones or piezoelectric pill transducers (PZPTs). Since hydrophones are intrusive sensors they impose a lower limit on the tube diameter (the tube diameter should be large compared to the hydrophone). Embedded PZPTs are typically spaced periodically imposing a limit on the resolution of the measured profile of the standing wave due to the finite size of the transducers. The advantages of the FOLI are the nonintrusive nature of the detection scheme, enhanced resolution, flexibility, and continuous scanning capabilities over a wide range of frequencies limited by the frequency response of the receiving photodiode and the properties of the membrane. The FOLI consisted of a Helium–Neon laser, a fiber optic beam splitter, a miniature lens, a photodiode, and a very thin reflective membrane which resides against the interior tube wall. The membrane is suspended by a small torus‐shaped magnet located on the exterior of the tube wall allowing continuous maneuverability in the vertical position of the membrane. The magnet also serves as the mount for the lens assembly.